Pengaruh Pemberian Masker Lemon dan Madu Terhadap Jerawat pada Akseptor Kb Suntik 1 Bulan di TPMB I Priode Mei Juni Kabupaten Purwakarta Tahun 2024 - Lusianawati, Evalina Fransisca; Heryani , Ida (Jurnal Sosial Teknologi, 2025)
Contraception is a way to prevent and delay pregnancy and plan the number of children to improve family welfare so that it can provide maximum attention and education to children. Each type of contraception used has its advantages. Hormonal changes that occur due to the use of injectable birth control can cause several disorders on the skin, such as acne. To find out the effect of giving honey lemon masks on acne in 1-month injectable birth control acceptors at TPMB I Purwakarta Regency in 2024. This study uses pre-experimental research with a White Control Group Design approach According to Notoatmodjo (2018), the Two Group Pretest Postest research design is a pre-experimental research design that uses a comparison group or interpretation given a honey lemon mask and a non-honey lemon maskThe picture of 30 mothers who accept Injectable Birth Control I months who use masks is only 26 mothers, the majority of whom are aged 20-35 years as many as 17 people, who are educated on average high school graduates as many as 14 people and mothers who use cosmetics more as many as 16 people.